B-Spline Impulse Response Functions of Rigid Bodies for Fluid-Structure Interaction Analysis - S. Zhou-Bowers; D. C. Rizos (Advances in Civil Engineering)
Reduced 3D dynamic fluid-structure interaction (FSI) models are proposed in this paper based on a direct time-domain B-spline boundary element method (BEM). These models are used to simulate the motion of rigid bodies in infinite or semi-infinite fluid media in real, or near real, time. B-spline impulse response function (BIRF) techniques are used within the BEM framework to compute the response of the hydrodynamic system to transient forces. Higher-order spatial and temporal discretization is used in developing the kinematic FSI model of rigid bodies and computing its BIRFs. Hydrodynamic effects on the massless rigid body generated by an arbitrary transient acceleration of the body are computed by a mere superposition of BIRFs. Finally, the dynamic models of rigid bodies including inertia effects are generated by introducing the kinematic interaction model to the governing equation of motion and solve for the response in a time-marching scheme. Verification examples are presented and demonstrate the stability, accuracy, and efficiency of the proposed technique.